Thermosensitive hydrogels as drug carriers for breast cancer treatment: a systematic review - Ikhsanudin, Azis; Sulaiman, Teuku Nanda Saifullah; Zai, Khadijah; Sudarmanto, Bambang Sulistyo Ari (Intelektual Pustaka Media Utama, 2023)
Thermo-sensitive hydrogel is a drug delivery system in breast cancer therapy, where the influence of environmental temperature changes will affect the characteristics of the polymer base. This study aimed to determine the effectiveness of polymers in thermo-sensitive hydrogel bases as drug carriers in breast cancer therapy and compared them with traditional intravenous drug release. This study used a systematic literature review (SLR) using selected reporting items for systematic review and meta-analysis guidelines (PRISMA) (P), based on predetermined inclusion criteria, namely English article, thermos-sensitive hydrogel, breast cancer, and original article. An initial database search yielded 618 articles, PubMed (241), Scopus (364), and the Directory of Open Access Journals (DOAJ) (36). To maintain the quality of the data studied in this article, researchers used inclusion and exclusion criteria, where the exclusion criteria used were non-English languages, review articles, proceedings, communications, video articles, and not open access. After the article screening process, 11 articles were obtained which would then be summarized in data extraction. The conclusion of this study shows that the thermos-sensitive hydrogel drug delivery system has advantages in drug release, where the drug will be released continuously, but also has the disadvantage of uncontrolled drug release.